Estudo de aplicação de compensador estático em derivação do tipo SVC na linha de transmissão Mesquita-Viana II em 500 KV - Bessa, Alcebíades Rangel (2015)
This paper presents the study of electrical system modeling connecting the Mesquita and Viana II of 500kV substation, evaluating the voltage regulation at Viana II substation with the application of SVC device. First the main characteristics of reactive compensators in electrical systems are presented, highlighting the SVC device. Then will appear the study area that connects the substations Mesquita and Viana II, with its electrical characteristics in the power flow scenario for the year of 2015. From this information the system will be modeled on the electromagnetic transient program PSCAD/EMTDC . The modeling of the electrical system as well as the operating scenarios was based on technical data obtained from ONS. From the system modeled in PSCAD/EMTDC is developed SVC device for stabilization of substation Viana II in his busbar at 500kV in 2015 scenario and also for load growth forecast by the year of 2021. The main contribution of this work is the electric system modeling of the SIN and the SVC device in PSCAD/EMTDC software as well as the analysis of the advantages gained by implementing this in the Viana II substation.